Apropriação da informação: um olhar sobre as políticas públicas sociais de inclusão digital - Carvalho, Angela Maria Grossi de [UNESP] (2010)
The historical change from an industrial society to a post-industrial one has deeply transformed the importance given to information. With new ways of processing information, new structures and technologies, the so called Information Society creates new possibilities for the economical, political, cultural and social sectors. However, there are also new barriers being raised by depriving the population from access and usability conditions for such new Information and Communication Technologies (ICT) and the whole structure offered by digital networks. By studying information, since its origin until its appropriation by an user, this thesis aims to discuss how digital exclusion may be solved with the participation of political and public spheres. The overall objective of this thesis is: Design a conceptual map that can contribute to the construction of Public Policy Ownership of information that takes into account the skills needed to embrace the knowledge generated by information technology and communication, particularly those used by programs digital inclusion, which, together with the scope of Information Science, contribute to the seizure interactive knowledge network. It is regarded as specific goal: to analyze the information and services available on the network to the public, especially in digital inclusion programs of the National Digital Inclusion of the Federal Government. Our methodology is bibliographical and documental exploratory research. Our research hypothesis considers that the actual public policies do not stimulte or contribute for the appropriation of information by the citizen, showing thus the frailty of governmental digital inclusion programs by aiming only the access to technologies and not active participation, development of handling habilities, informational exploration... (Complete abstract click electronic access below)